2020
DOI: 10.1109/access.2020.2994283
|View full text |Cite
|
Sign up to set email alerts
|

3D Face Tracking Using Stereo Cameras: A Review

Abstract: This review considers previous research, regarding the background and applications of 3D facetracking systems with a focus on stereo camera-based systems. Stereo cameras are less expensive than laser ranging systems, and they are widely available on devices such as smart phones. This review aims to spur further development and applications of face tracking in this domain. Many studies on face tracking have used concepts such as the Kanade-Lucas-Tomasi method, particle filters, tracking-learning-detecting, prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 87 publications
(256 reference statements)
0
6
0
Order By: Relevance
“…Actual-time projection of 3D and 2D virtual items into the real world is the essence of Augmented Reality (AR) (Alqahtani et al, 2020). Additional Reality or Augmented Reality (AR) is a technology that mixes virtual two-and three-dimensional items with real time projections onto a three-dimensional sphere (Akhunova, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Actual-time projection of 3D and 2D virtual items into the real world is the essence of Augmented Reality (AR) (Alqahtani et al, 2020). Additional Reality or Augmented Reality (AR) is a technology that mixes virtual two-and three-dimensional items with real time projections onto a three-dimensional sphere (Akhunova, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The authors Alqahtani et al [16] reported a review paper entitled "3D face tracking using stereo cameras: A review". Applications of 3D face-tracking systems with a focus on stereo camera-based systems was postulated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[11] tracks deformable objects with point clouds and the use of probabilistic methods, it also manages to simulate the object's behaviour in real time using a previous model of the object. Other 3D deformable object trackers accomplish efficiency specialising in specific target objects like faces [12], hands [13] or full bodies [14]. Non-rigid SLAM systems like [15] (RGB-D) and [16] (monocular) manage to solve camera location and nonrigid environment characterisation, nonetheless, they do not tackle the segmentation problem.…”
Section: A Related Workmentioning
confidence: 99%